Microwave dielectric properties of Dy2O3 substituted BiNbO4 ceramics - Lim, Hyuk; Oh, Young-Jei (JAPAN SOC APPLIED PHYSICS, 2006)
The microwave dielectric properties of Bi1-x,DxNbO4 ceramics were investigated as a function of Dy3+ substitution (0 <= x <= 0.1). Bi1-xDyxNbO4 compositions prepared at low temperatures (900-960 degrees C). A single orthorhombic (alpha-BiNbO4) phase in all Bi1-xDyxNbO4 compositions was obtained for the whole sintering temperature range. The decrease in the dielectric constant of the Bi1-xDyxNbO4 ceramics with increasing Dy content is attributed to the decrease in polarizability as Dy is substituted to the Bi site. The decrease in the temperature coefficient of the resonant frequency is due to the distortion of the oxygen octahedra.
Keywords: TEMPERATURE-COEFFICIENT; BOND VALENCE